2018
DOI: 10.1016/j.scitotenv.2017.09.092
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of environmental change on the radial growth of co-occurring beech and fir trees across Europe

Abstract: Under predicted climate change, native silver fir (Abies alba) and European beech (Fagus sylvatica) are the most likely replacement species for the Norway spruce (Picea abies) monocultures planted across large parts of continental Europe. Our current understanding of the adaptation potential of fir-beech mixed forests to climate change is limited because long-term responses of the two species to environmental changes have not yet been comprehensively quantified. We compiled and analysed tree-ring width (TRW) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 48 publications
10
61
0
Order By: Relevance
“…In accordance with the second part of our hypothesis, beech displayed more negative growth (BAI) trends compared to fir across our sites but the temporal trajectories of BAI complementarity were positive and did not differ between the two species. Similarly, another European-wide study has reported declining growth trends in European beech but not in silver fir growing in mixed stands for a similar period, concluding that fir is less susceptible to warmer and drier conditions than beech (Bosela et al, 2018). Our findings with regard temporal trends of complementarity and growth should be interpreted with caution, however, as we analyzed only the most recent 16 years.…”
Section: Mixing Effects On Overall Growth Performance and Over Timementioning
confidence: 58%
“…In accordance with the second part of our hypothesis, beech displayed more negative growth (BAI) trends compared to fir across our sites but the temporal trajectories of BAI complementarity were positive and did not differ between the two species. Similarly, another European-wide study has reported declining growth trends in European beech but not in silver fir growing in mixed stands for a similar period, concluding that fir is less susceptible to warmer and drier conditions than beech (Bosela et al, 2018). Our findings with regard temporal trends of complementarity and growth should be interpreted with caution, however, as we analyzed only the most recent 16 years.…”
Section: Mixing Effects On Overall Growth Performance and Over Timementioning
confidence: 58%
“…Yet another potential driver of the higher foliar P in silver fir needles of the CRO stand may be (6) the length of the vegetation period that is affected either by altitudes (EMM vs. CON) or by a more southerly location of the CRO forest site with shorter day length (21st of June: 17:03 h at the CON and 15:30 h at the CRO forest site (https ://www.sunri se-and-sunse t.com)). In addition, (7) the significant warming trend from 1990 to 2010 is accompanied by a decline in beech growth, whereas silver fir growth increased (Bosela et al 2018). As at the CRO forest complementation of basal area index of silver fir by beech was positive (around 40%), that of beech by silver fir was negative (approx.…”
Section: P Nutrition Of Abies Alba Needlesmentioning
confidence: 99%
“…The downregulation of photosynthesis after the extreme drought and heat wave, which hit Central Europe in the summer of 2003, reduced the productivity of beech forests (Bosela et al 2018;Leuzinger et al 2005;van der Werf et al 2007). A decline in beech productivity in response to drought stress was also recorded in Mediterranean Europe (Jump et al 2006;Piovesan et al 2008), though populationspecific vulnerability to drought might be mitigated to some extent by acclimation (Dittmar et al 2003;Pretzsch et al 2020a;Tegel et al 2014;Tognetti et al 2014).…”
Section: Introductionmentioning
confidence: 99%